Investigation of the levels of different salivary stress markers in chronic periodontitis patients - Develioglu, Hakan; Korkmaz, Saygin; Dundar, Serkan; Schlagenhauf, Ulrich (Elsevier B.V., 2020)
Background and aim: In this study, we aimed to determine the salivary levels of cortisol, ?-amylase, ?-endorphin, and chromogranin (CgA) in saliva and to investigate their relationship with periodontitis. Methods: Thirty-seven female and 43 male periodontitis patients who presented to the Periodontology Department of the XXX University Faculty of Dentistry participated in the study. The individuals were divided into three groups: mild, moderate, or severe chronic periodontitis. Plaque index (PI), gingival index (GI), clinical attachment loss (CAL), and probing depth (PD) measurements were recorded for all the participants. All participants underwent the State–Trait Anxiety Inventory test (STAI 1 and 2). Between 09:00 and 11:00 a.m., saliva samples from the participants were collected into tubes within an average of five minutes. Results: Higher cortisol measurements were detected in the saliva samples of participants with severe chronic periodontitis than in those who had mild chronic periodontitis (P < 0.05). There were statistically significant age differences among patients with mild–moderate, moderate–severe, and mild chronic periodontitis, the severity of the disease increasing with age (P < 0.05). There was also a positive correlation between STAI 1 stress scores and cortisol levels. Similarly, there was a positive correlation between CAL and cortisol levels (P < 0.05). However, a significant difference was found among groups only in terms of salivary cortisol levels (P < 0.05). Conclusion: Within the limitations of this study, there was found to be a relationship between saliva cortisol levels and periodontitis and between salivary cortisol levels and stress. © 2020
Keywords: Clinical attachment loss; Periodontitis; Salivary cortisol; Salivary stress markers